Self-Parking Car - Mohammad Abuarqoub, Mohammad; Shaheen, Islam (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2021)
Parking is usually a driver’s worst nightmare because, it not only requires the driver’s skills but also increases the possibility of other drivers bumping into their parked vehicle. Autonomous car parking was introduced to encounter the parking problems. Self-parking Car technology is a car that guides itself without human conduction. In this project, we developed the car's brain by Arduino microcontroller, so that it helps the driver to detect the right place to stop the car inside a narrow area between other cars without a collision, through sensors to detect the appropriate space , which is the ultrasonic and also to measure the distance needed to advance and return, and also the encoder was used to measure the number of turns The engine that works to drive and move the wheels, this motor engine controlled by Arduino by using driver to link between Arduino and DC motor.
no of pages 36, هندسة حاسوب 16/2021
Keywords: Parkings Car